Study of Effect of Climate Change on Potential Evapotranspiration in Arid Areas Using Geostatistics (Case Study: Yazd Province) - E. Mahdavie Nezhad; S. Z. Hosseini; H. Maleki Nezhad; M.A. Asadi (مدیریت بیابان, 2019)
In water systems, precipitation is considered as input and evaporation as the output of the system. Water availability can be estemated from the relationship between these two factors. Therefore, evapotranspiration is the most important factor after precipitation in hydrological cycle. Evapotranspiration is influenced by climatic parameters such as temperature, wind, humidity and sunshine hours. In this research, changes in PET and effective climatic parameters, influencing on PET changes including temperature, wind, humidity, and solar radiation were investigated. For this purpose, PET in 14 weather stations of Yazd province were calculated using the FAO-Penman-Monteith method. Due to the lack of sunshine hours data in some stations, regeneration of the incomplete data was done by using regression method. Due to the lack of wind speed data at some stations, their reconstruction by using data from other stations was done by applying three methods of Inverse Distance Weighted, Kriging and Cokriging. After calculating potential evapotranspiration, PET data were zoned and their monthly and annual trends tested by Mann-Kendall test. Despite occurrence of climate change and increasing of temperature in 13 stations out of the 14 stations, it is expected an increase in potential evapotranspiration in past few decades, while, there is a decreasing trend in PET. Investigating on the effective parameters in potential evapotranspiration showed that wind speed has declined in the last few decades, and despite of an increase in temperature, potential evapotranspiration rate reduces in 64.3% of the stations. General trend of evapotranspiration was -0.86 in this period, which indicates a decrease in evapotranspiration in the Yazd province.